Effectiveness of different irrigant activation techniques in removing smear layer: a scanning electron microscope study - Mahmoud, Okba; Alsanafi, Sura; AlKhazraji, Hajir; Alyouzbaky, Karwan (Journal of Baghdad College of Dentistry, 2026)
Background: This study evaluated the effectiveness of Laser-Activated Irrigation (LAI), XP-Endo Finisher, and Endo Activator in removing the smear layer from root canal walls by assessing dentinal tubule opening in the coronal, middle, and apical thirds using scanning electron microscopy. Materials and Methods: Thirty single-rooted human anterior teeth were decoronated to a standardized length and prepared using the WaveOne Gold primary rotary system. The samples were randomly divided into three experimental groups (n=10): LAI, XP-Endo Finisher, and Endo Activator, along with a control group irrigated using a conventional syringe technique. The roots were split longitudinally and examined under SEM at 1000x magnification. Images were obtained from the coronal, middle, and apical thirds. Data were analyzed using the Kruskal–Wallis test, with statistical significance set at p